SOSIALISASI PROTOKOL KESEHATAN 5M DI MASA PANDEMI SECARA DARING - Irfan Ihsani; Wita Meutia; Prima Jiwa Osly; Farhan Rafliansyah (Program Studi Teknik Sipil Fakultas Teknik Universitas Pancasila, 2022)
Various efforts have been made to reduce the rate of the spread of Covid. In Indonesia, the government has made a health protocol known as 5M which consists of washing hands, wearing masks, maintaining distance, staying away from crowds, and reducing mobility (Ministry of Health of the Republic of Indonesia). The purpose of this Community Service is to increase public understanding regarding the 5M health protocol. This activity was carried out by distributing 5M posters online for residents of Jl. J. Buntu RT. 005 RW.012 Kec. Tebet, Kel. Kebon Baru, City of Jakarta, DKI Jakarta. With the distribution of posters related to the 5M health protocol online, residents' understanding of health protocols increases and residents are expected to follow the health protocols. Keywords: 5M, COVID-19, Health Protocol